Novel frameshift variant in the PCNT gene associated with Microcephalic Osteodysplastic Primordial Dwarfism (MOPD) Type II and small kidneys - D. Hettiarachchi; S. M. V. Subasinghe; G. G. Anandagoda; Hetalkumar Panchal; P. S. Lai; V. H. W. Dissanayake (BMC, 2022)
Abstract Background Microcephalic Osteodysplastic Primordial Dwarfism (MOPD) Type II is an autosomal recessive condition encompassing a heterogeneous group of disorders characterized by symmetrical growth retardation leading to dwarfism, microcephaly, and a range of multiple medical complications including neurovascular diseases. Biallelic pathogenic variants in the pericentrin gene (PCNT) have been implicated in its pathogenesis. Case presentation We performed whole-exome sequencing to ascertain the diagnosis of a 2 year and 6 months old boy who presented with severe failure to thrive, microcephaly, and facial gestalt suggestive of MOPD Type II which included features such as retrognathia, small ears, prominent nasal root with a large nose, microdontia, sparse scalp hair, bilateral fifth finger clinodactyly. He had a small ostium secundum atrial septal defect and bilaterally small kidneys. Microcephalic Osteodysplastic Primordial Dwarfism (MOPD) Type II was confirmed based on a pathogenic compound heterozygous frameshift variant in the PCNT gene c.5059_5060delAA | p. Asn1687fs (novel variant) and c.9535dup (p. Val3179fs). His parents were found to be heterozygous carriers for the variants. Conclusion We report a novel frameshift variant in the PCNT gene and a previously unreported phenotype for Microcephalic Osteodysplastic Primordial Dwarfism (MOPD) Type II.